STREPTOZOTOSİN İLE DİYABET OLUŞTURULAN RATLARDA ALFA LİPOİK ASİTİN BEYNİN FARKLI BÖLGELERİNDEKİ NÖRON SPESİFİK ENOLAZ, S-100B PROTEİNİ, LİPİD PEROKSİDASYONU VE GLUTATYON ÜZERİNE ETKİSİ - SARICALI, MEHMET (Fırat Üniveristesi, 2004)
Bu deney ağırlıkları 200-250 gram olan toplam 45 rat üzerinde yapıldı. Ratlar 3 gruba ayrıldı. Kontrol grubundaki (n=15) ratlara deney süresince 0,5 cc/gün serum fizyolojik intraperitoneal (i.p.) verildi. Diabet grubuna (n=15) 50 mg/kg streptozotosin (STZ) i.p. verilerek ratlar diabetik hale getirildiler. Diabet + alfa lipoik asit (Diabet+ALA) grubuna (n=15) 50 mg/kg STZ i.p. verilerek diabetik hale getirildikten sonra 100 mg/kg/gün ALA i.p. verildi. 6 hafta sonunda ratlar dekapite edildi. STZ ile diabet oluşturulan grupta kontrol grubuna göre nöron spesifik enolaz (NSE) değeri hipokampusda (pO.001), korteksde (pO.001) ve serebellumda (pO.001) anlamlı artış, S100B değeri hipokampusda (p<0.01), korteksde (p<0.001) ve serebellumda (p<0.001) anlamlı artış, LPO değeri hipokampusda (p<0.001) ve korteksde (p<0.01) anlamlı artış gösterirken, GSH değeri hipokampusda (p<0.05) ve korteksde (p<0.05) anlamlı azalma gösterdi. Diabet + ALA grubunda diabet grubuna göre NSE değeri hipokampusda (pO.001), korteksde (p<0.01) ve serebellumda (p<0.01) anlamlı azalma, S100B değeri hipokampusda (p<0.05), korteksde (pO.001) ve serebellumda (p<0.05) anlamlı azalma, LPO değeri hipokampusda (p<0.01) ve korteksde (pO.01) anlamlı azalma, GSH değeri hipokampusda (p<0.05) ve korteksde (p<0.05) anlamlı artış gösterdi. Sonuç olarak; artan nöronal ve gliaİ markırlann (NSE ve S100B) artan LPO miktarları ile orantılı olduğu, glial reaktivitenin diabette oksidatif stresle ilişkili olabileceği, deneysel diabette reaktif gliozis geliştiği ve bunun antioksidan ALA tarafından önlendiği gözlenmiştir. Bu sebeple diabette oluşabilecek nöronal ve glial hasara karşı ALA'in bir nöroprotektör olabileceğini düşünmekteyiz. Anahtar Kelimeler: Diabet, Nöron spesifik enolaz, S100B, Lipid peroksidasyonu, Alfa lipoik asit

The Effect of Alpha Lipoic Acid on Neuron Specific Enolase, S100B Protein, Lipid Peroxidation and Glutathione in the Various Brain Regions of Streptozotocine-Induced Diabetic Rats This experiment was performed on 45 rats each weighing 200-250 grams. Rats were divided into 3 groups. Rats in the control group (n=15) were given 0.5 cc/day physiologic saline intraperitonealy (i.p.) during the test period. Rats in diabetic group (n=15) were given 50 mg/kg i.p. streptozotocin (STZ) to make them diabetic. Rats in diabetes + alpha lipoic acid (diabetes + ALA) group (n=15) were given 50 mg/kg i.p. STZ to make them diabetic and then given 100 mg/kg/day i.p. ALA. Six weeks later all of the rats were decapitated. Compared with control group the neuron specific enolase (NSE) value was significantly increased in hypocampus (pO.OOl), cortex (p<0.001) and cerebellum (pO.001), the S100B value was increased in hypocampus (p<0.01), cortex (pO.OOl) and cerebellum (p<0.001), the lipid peroxidation (LPO) value was significantly increased in hypocampus (pO.OOl), cortex (p<0.01) and the glutathione (GSH) value was significantly decreased in hypocampus (p<0.05) and cortex (p<0.05) in diabetic group which was formed by STZ. Compared with diabetic group the NSE value in hypocampus (pO.OOl), cortex (pO.01) and cerebellum (pO.01) was significantly decreased, the S100B value in hypocampus (pO.05), cortex (pO.OOl) and cerebellum (p<0.05) was significantly decreased, the LPO value in hypocampus (pO.01), cortex (pO.01) was significantly decreased and the GSH value in hypocampus (pO.05) and cortex (pO.05) was significantly increased in diabetes + ALA group. As a conclusion, it was observed that increase in neuronal, and glial markers ( NSE and S100B ) was in proportion with increase in LPO value; glial reactivity might be related with diabetic oxidative stress; reactive gliosis developed in experimental diabet and this was prevented by ALA which is an antioxidant daig. That is why we think that ALA may be a neuroprotector against in neural and glial injury of diabet. Key Words: Diabetes, Neuron specific enolase, S100B, Lipid peroxidation, Alpha lipoic acid
The effect of alpha lipoic acid on neuron specific enolase, S-100B protein, lipid peroxidation and glutathione in the various brain regions of streptozotocine-induced diabetic rats
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Endokrinoloji ve Metabolizma Hastalıkları; Endocrinology and Metabolic Diseases